Effectiveness of Alcohol, Smoking, and Substance Involvement Screening Test-Linked Brief Intervention on Harmful and Hazardous Alcohol Use in Nigerian Semirural Communities: A Non-Randomized Intervention Study - Lasebikan, Victor; Ola, Bolanle Adeyemi; Ayinde, Olatunde O. (Frontiers in Psychiatry, 2017)
Objective: To determine to examine the effectiveness of Alcohol, Smoking and Substance Involvement Screening test Linked Brief Intervention on hazardous and harmful alcohol use in semi-rural settings in Nigeria. Methods: A single arm non-randomized intervention study was conducted in two semi-rural local government area of Oyo state, Nigeria. Participants included 1203 subjects 15 years and older, recruited between October and 2010 and April 2011. Score of 0-10 were classified as lower risk scores, 11-26 as moderate risk, and 27+ as high risk. Main outcome measure was the Change in ASSIST scores from baseline at 3 and 6 months after intervention. Results: Mean ASSIST score significantly reduced at 3 months versus baseline for all categories irrespective of level of risk score and at 6 months versus 3 months only for those with lower risk score. Conclusion: ASSIST linked SBIRT for unhealthy alcohol use should be integrated into community care services in Nigerian semi-rural communities.